Asymmetric perceptions of the economy: Media, firms, consumers, and experts - Konstantin Kholodilin; Christian Kolmer; Tobias Thomas; Dirk Ulbricht (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This article sheds light on the interaction of media, economic actors, and economic experts. Based on a unique data set of 86,000 news items rated by professional analysts of Media Tenor International and survey data, we first analyze the overall tone of the media, consumers', firms', and economic experts' opinions on the state and outlook of the economy. Second, we assess the protagonist's ability at correctly predicting GDP. Third, we use Granger causality tests to uncover who is influencing whom when it comes to the formation of opinions on the economy. We find that media reports have a significant negative bias. The economic sentiment of the media, consumers and firms does not reflect the actual situation. Finally, we find that media sentiment is not influenced by any other actor. In contrast, media appear to affect all other actors.
Keywords: E32; E37; L82; 330; media bias; consensus forecasts; consumer and business sentiment